Manufacturing method of lithium tantalate substrate
By introducing an annealing step and controlled reduction process, the method addresses pyroelectricity-induced defects in lithium tantalate substrates, ensuring stable production of substrates with uniform conductivity and reduced defects, enhancing the quality of surface acoustic wave devices.
Patent Information
- Application Number
- JP2021037064
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-03-09
AI Technical Summary
Existing methods for manufacturing lithium tantalate substrates fail to adequately address the issues of pyroelectricity-induced charge-up and resulting discharge, leading to electrode destruction and substrate cracks, while also causing reduction defects like white and black spots, which affect the uniformity and conductivity of the substrates.
Incorporating an annealing step at temperatures between 500°C and the Curie temperature of lithium tantalate in an air atmosphere after slicing and before reduction, followed by a reduction process using a mixture of aluminum powder and aluminum oxide powder, with continuous inert gas supply to remove organic residues and ensure uniform reduction.
This method stabilizes the production of lithium tantalate substrates with excellent electrical properties by eliminating reduction defects and achieving uniform conductivity, thereby improving the yield and quality of surface acoustic wave devices.
Smart Images

Figure 0007604955000002 
Figure 0007604955000003 
Figure 0007604955000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a lithium tantalate substrate, which includes a slicing step of slicing a lithium tantalate single crystal to form a single crystal wafer, and a reduction step of reducing the obtained single crystal wafer, and in particular to a method for manufacturing a lithium tantalate substrate that can stably manufacture a lithium tantalate substrate having excellent electrical characteristics and no color unevenness (uneven reduction) by avoiding poor reduction (insufficient reduction) known as white spots and poor reduction (excessive reduction) known as black spots. [Background technology]
[0002] Lithium tantalate (sometimes abbreviated as LT) single crystal is a ferroelectric material with a melting point of about 1650°C and a Curie temperature of about 600°C, and lithium tantalate substrates (LT substrates) manufactured using this single crystal are mainly used as surface acoustic wave (SAW) filter materials for use in transmitting and receiving devices in mobile phones. With the increasing frequency of mobile phones and the spread of Bluetooth (registered trademark) (2.45 GHz), a wireless LAN for various electronic devices, it is predicted that there will be a rapid increase in SAW filters in the frequency range of around 2 GHz in the future.
[0003] The SAW filter has a structure in which a pair of comb electrodes made of a thin metal film such as Al or Cu is formed on an LT substrate, and this comb electrode plays an important role in determining the characteristics of the device. The comb electrodes are formed by forming a thin metal film on the LT substrate by sputtering, and then removing unnecessary portions by etching using photolithography technology, leaving a pair of comb patterns.
[0004] The method for growing the LT single crystal and the manufacturing process of the LT substrate applied to the SAW filter will be described below.
[0005] First, LT single crystals are industrially produced by growth methods such as the Czochralski method (CZ method), and the obtained LT single crystals are colorless and transparent or have a highly transparent pale yellow color.
[0006] After growth, any ends of the single crystal that are too small in diameter while still in the ingot state are cut off, and the LT single crystal undergoes heat treatment to remove distortion and poling treatment to induce polarization before being handed over to the processing step.
[0007] In the processing process, the material is machined into a cylinder slightly thicker than the final product in a cylindrical grinding process, and then sliced into disks using a wire saw in a slicing process to become single crystal wafers.
[0008] The resulting single crystal wafer is then finished to the product diameter in a beveling process, and the edges are chamfered. After that, it is turned into a LT substrate through mechanical processing such as lapping and polishing. The finally obtained LT substrate is almost colorless and transparent, and its volume resistivity is approximately 10 14 ~10 15 It is about Ω·cm.
[0009] However, in the LT substrate obtained in this manner, during the surface acoustic wave element (SAW filter) manufacturing process, due to the pyroelectricity that is a characteristic of the LT single crystal, electric charge builds up on the substrate surface due to temperature changes during the process. This causes discharges that destroy the comb-shaped electrodes formed on the substrate surface and even causes the substrate to crack, resulting in a decrease in yield in the element manufacturing process.
[0010] Therefore, in order to eliminate the problems caused by the pyroelectricity of LT single crystals, techniques for increasing electrical conductivity have been proposed. For example, Patent Document 1 proposes a method for increasing electrical conductivity by reducing sliced single crystal wafers in a reducing atmosphere of a gas selected from argon, water, hydrogen, nitrogen, carbon dioxide, carbon monoxide, oxygen, and combinations thereof, and Patent Document 2 proposes a method for reducing the sliced single crystal wafers by embedding them in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder).
[0011] In addition, the single crystal wafer with increased conductivity absorbs light due to the oxygen vacancies introduced. The color tone of the single crystal wafer observed is reddish brown in transmitted light and black in reflected light, so the reduction process that increases conductivity is also called blackening, and this change in color tone is called blackening. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Japanese Patent Application Publication No. 11-92147 [Patent Document 2] Patent No. 4063191 Summary of the Invention [Problem to be solved by the invention]
[0013] However, unlike lithium niobate single crystals, which have a relatively low melting point of about 1250°C, when the method of Patent Document 1 is applied to LT single crystals, which have a high melting point of about 1650°C, there is a problem that the conductivity of the single crystal wafer does not increase sufficiently, and defects due to pyroelectricity are not sufficiently improved. In recent years, in order to improve the yield in the manufacturing process of surface acoustic wave elements (SAW filters), there has been a demand to lower the volume resistivity, which is a property of LT single crystals. For example, 9 There is a demand for a value of less than (Ω·cm).
[0014] On the other hand, the method of Patent Document 2, in which sliced single crystal wafers are embedded in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder) and then reduced, is 1×10 9 This has the advantage of being able to obtain the desired volume resistivity of less than (Ω·cm).
[0015] However, uniformity within the substrate surface is required to avoid defects due to pyroelectricity, but when reduction processing is performed using the method of Patent Document 2, poor reduction known as white spots (insufficient reduction) and poor reduction known as black spots (excessive reduction) can occur. White spots are dot-like areas that appear white to the naked eye, and substrates with white spots are deemed defective because reduction is insufficient and suppression of pyroelectricity is insufficient. Black spots are also deemed defective because they are excessively reduced compared to other areas.
[0016] The present invention has been made in view of these problems, and an object of the present invention is to provide a method for producing a lithium tantalate substrate, which can stably produce a lithium tantalate substrate having excellent electrical characteristics and no color unevenness (uneven reduction) by avoiding poor reduction (insufficient reduction) known as white spots and poor reduction (excessive reduction) known as black spots, when a sliced single crystal wafer is embedded in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder) and subjected to a reduction treatment. [Means for solving the problem]
[0017] In order to solve this problem, the present inventors conducted an intensive analysis of the causes of poor reduction (insufficient reduction) known as white spots and poor reduction (excessive reduction) known as black spots when sliced single crystal wafers are embedded in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder) and then subjected to a reduction process, and as a result, discovered that the slicing process using a wire saw is related to the causes.
[0018] That is, when slicing a cylindrical LT single crystal using a wire saw, a method of slicing while supplying a working fluid containing abrasive grains to the contact part between the wire and the LT single crystal (loose abrasive grain method), or a method of slicing using a wire with abrasive grains fixed in advance (fixed abrasive grain method) is used. In the former free abrasive grain method, a slurry (working fluid) in which an oil agent is mixed with abrasive grains is used, while the latter fixed abrasive grain method uses a working fluid in which cutting oil or the like is added to water, so it is thought that oil components are attached to the surface of the single crystal wafer after the slicing process. In addition, the single crystal wafer after the slicing process is washed with a detergent, but it is thought that some of the detergent remains on the surface of the single crystal wafer after washing, and further, organic matter such as sebum due to handling is also attached, and it has been found that these oil components, detergent, sebum, and other organic matter are the cause of the reduction failure. Therefore, it has been found that when the single crystal wafer is annealed in an air atmosphere in the stage before the reduction process, the oil components, detergent, sebum, and other organic matter are removed, and the color unevenness due to the above-mentioned white spots and black spots is eliminated. The present invention has been completed through such technical discoveries and analysis.
[0019] That is, the first invention according to the present invention is: A method for producing a lithium tantalate substrate, comprising: a slicing step of slicing a lithium tantalate single crystal to obtain a single crystal wafer; and a reduction step of reducing the obtained single crystal wafer, the above No reduction treatment has been applied The method is characterized in that an annealing step is provided between the slicing step and the reducing step, in which the single crystal wafer is annealed in an air atmosphere at a temperature of 500° C. or higher and lower than the Curie temperature of the lithium tantalate single crystal.
[0020] The second aspect of the present invention is In the method for producing a lithium tantalate substrate according to the first aspect of the present invention, The method is characterized in that a plurality of single crystal wafers are stacked to form a single crystal wafer polymer, one or a plurality of single crystal wafer polymers are placed on a plate or tray, and then the plate or tray on which the single crystal wafer polymer is placed is placed in a heating furnace under an atmospheric atmosphere to perform the annealing treatment; The third invention is In the method for producing a lithium tantalate substrate according to the first or second invention, The treatment time of the annealing step is 24 to 48 hours, The fourth invention is In the method for producing a lithium tantalate substrate according to any one of the first to third aspects of the present invention, The slicing step is characterized in that it is a slicing process using a wire saw.
[0021] Next, the fifth aspect of the present invention is In the method for producing a lithium tantalate substrate according to any one of the first to fourth aspects of the present invention, the reduction step is a reduction treatment in which the single crystal wafer is embedded in a mixed powder of aluminum powder and aluminum oxide powder filled in a container, the container is placed in a heating furnace, and then heated at a temperature lower than the Curie temperature of the lithium tantalate single crystal; The sixth invention is In the method for producing a lithium tantalate substrate according to the fifth aspect of the present invention, The reduction treatment is carried out while continuously supplying and discharging an inert gas into the heating furnace under an atmospheric condition. Effect of the Invention
[0022] According to the method for producing a lithium tantalate substrate of the present invention, Between a slicing process in which the lithium tantalate single crystal is sliced to obtain a single crystal wafer and a reduction process in which the single crystal wafer is reduced, the above-mentioned reduction step is performed in an air atmosphere at a temperature of 500° C. or higher and lower than the Curie temperature of the lithium tantalate single crystal. No reduction treatment has been applied Since an annealing process for annealing the single crystal wafer is provided, Organic matter such as oil components remaining on the surface of the single crystal wafer is removed by the annealing treatment, and reduction defects (insufficient reduction) known as white spots and reduction defects (excessive reduction) known as black spots are avoided, making it possible to stably produce lithium tantalate substrates that are free of color unevenness (reduction unevenness) and have excellent electrical properties. [Brief description of the drawings]
[0023] [Figure 1] A schematic perspective view showing three sets of single crystal wafers placed on a stainless steel tray. [Diagram 2] FIG. 1 is an explanatory diagram showing a state in which a plurality of aluminum containers, each containing a single crystal wafer embedded in a mixture of aluminum powder and aluminum oxide powder, are housed in a large carbon container. [Diagram 3] FIG. 1 is a schematic perspective view showing a configuration of a multi-wire saw device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The embodiment of the present invention will be specifically described.
[0025] (1) Slicing with a wire saw (1-1) Multi-wire saw device FIG. 3 is a schematic perspective view showing the configuration of the multi-wire saw device.
[0026] That is, the multi-wire saw device 50 is equipped with a plurality of rollers R (R1, R2), a plurality of wire rows 52 (wire group) formed by winding a wire 51 between the plurality of rollers R multiple times, and a crystal holding section 53 that holds a cylindrical LT single crystal 60, and is a device that cuts the LT single crystal 60, which is to be sliced, into a plurality of single crystal wafers using the wire row 52.
[0027] As shown in FIG. 3, the crystal holding part 53 is composed of a slice bed 53a to which the LT single crystal 60 is adhesively fixed, and a sheet material 53b, and the crystal holding part 53 is fixed to a saddle 55 via the sheet material 53b.
[0028] (1-2) Loose abrasive method The free abrasive method slices the LT single crystal 60 while supplying a machining fluid containing abrasive grains to the contact area between the wire 51 and the LT single crystal 60. A slurry of abrasive grains (e.g., SiC) and oil (e.g., a compound selected from polyhydric alcohols, polyhydric alcohol condensates, and polyhydric alcohol derivatives, aromatic carboxylic acids, basic substances that neutralize the aromatic carboxylic acids and make them water-soluble, and water, etc.) is sprayed from a nozzle 54 shown in FIG. 3 and adheres to the traveling wire row 52 to slice the LT single crystal 60.
[0029] (1-3) Fixed abrasive method The fixed abrasive method is a method in which the LT single crystal 60 is sliced using a wire 51 to which abrasive grains (e.g., diamond) have been previously fixed (electroplated, etc.). The slurry used in the above-mentioned free abrasive method is not necessary, but instead, a machining fluid consisting of water to which cutting oil (for example, consisting of glycols such as ethylene glycol and propylene glycol, organic acids such as saturated fatty acids, unsaturated fatty acids, aromatic carboxylic acids, and basic agents such as alkylamines that dissolve in water and exhibit basicity) is added is sprayed from a nozzle 54 to slice the LT single crystal 60.
[0030] (2) Insufficient reduction As described above, organic matter such as the oil components of the oil agent, detergent, sebum, etc. remain partially on the surface of single crystal wafers sliced using the free abrasive method, and organic matter such as the oil components of the cutting oil, detergent, sebum, etc. also remain partially on the surface of single crystal wafers sliced using the fixed abrasive method, and it is believed that the organic matter remaining on the surface of the single crystal wafer is the cause of poor reduction.
[0031] (2-1) Insufficient reduction (insufficient reduction) When a single crystal wafer containing residual organic matter such as oil components, detergent, or sebum is embedded in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder) and subjected to a reduction process, the oxygen contained in the organic matter oxidizes the Al powder present near the single crystal wafer, robbing the Al powder of its ability to act as a reducing agent, causing poor reduction and resulting in color unevenness (uneven reduction) known as white spots.
[0032] (2-2) Insufficient reduction (excessive reduction) When a single crystal wafer containing residual organic matter such as oil, detergent, or sebum is embedded in a mixture of aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder) and then reduced, the carbon and hydrogen components contained in the organic matter are burned (oxidized) and the oxygen in the atmosphere in which the single crystal wafer is embedded is consumed, causing localized reduction, which is thought to result in color unevenness (uneven reduction) known as black spots.
[0033] (3) The present invention The present invention provides a method for manufacturing a lithium tantalate substrate that avoids insufficient reduction (insufficient reduction) known as white spots and insufficient reduction (excessive reduction) known as black spots.
[0034] That is, the present invention relates to a method for producing a lithium tantalate substrate, which includes a slicing step of slicing a lithium tantalate single crystal to obtain a single crystal wafer, and a reduction step of reducing the obtained single crystal wafer, the method comprising the steps of: reducing the lithium tantalate single crystal wafer in an air atmosphere at a temperature of 500° C. or higher and lower than the Curie temperature of the lithium tantalate single crystal; The above reduction treatment has not been applied The method is characterized in that an annealing step for annealing the single crystal wafer is provided between the slicing step and the reducing step.
[0035] Furthermore, according to the present invention, the annealing process burns and removes organic matter such as oil components remaining on the surface of the single crystal wafer, thereby preventing poor reduction (insufficient reduction) known as white spots and poor reduction (excessive reduction) known as black spots, making it possible to stably produce lithium tantalate substrates that are free of color unevenness (uneven reduction) and have excellent electrical properties.
[0036] Hereinafter, each step of the manufacturing method for the LT substrate according to the present invention will be described.
[0037] (A) Annealing process This process is a step prior to the reduction treatment of the sliced single crystal wafer, in which the single crystal wafer is annealed in an air atmosphere at a temperature of 500° C. or higher but lower than the Curie temperature of the lithium tantalate single crystal, to combust and remove organic matter such as the oil components, detergent, and sebum remaining on the surface of the single crystal wafer from the surface of the single crystal wafer.
[0038] For example, as shown in Fig. 1, a plurality of single crystal wafers 1 are stacked to form a single crystal wafer polymer 10, and one or a plurality of single crystal wafer polymers 10 (three sets of single crystal wafer polymers 10 are illustrated in Fig. 1) are placed on a plate or stainless steel tray 2, and then the plate or stainless steel tray 2 on which the single crystal wafer polymer 10 is placed is placed in a heating furnace (not shown) under atmospheric air for annealing. Note that instead of the method of forming the single crystal wafer polymer 10, the single crystal wafers may be propped up one by one in a storage case without being stacked, and the storage case may be placed on the plate or tray for annealing.
[0039] The treatment time for the annealing step (annealing time) is preferably 24 hours to 48 hours, and more preferably 40 hours to 48 hours.
[0040] (B) Reduction process This step is a step in which the single crystal wafer that has been subjected to the annealing step is subjected to a reduction treatment to adjust the volume resistivity of the single crystal wafer to a desired value.
[0041] For example, as shown in FIG. 2, an aluminum container 21 is filled with aluminum powder (Al powder) and aluminum oxide powder (Al2O3 powder), and the single crystal wafers 1 that have undergone the above-mentioned annealing process are embedded in a mixed powder 22 of these. At the same time, a plurality of aluminum containers 21 with the single crystal wafers 1 embedded therein are housed in a large container 23 made of carbon, and this large container 23 is placed in a heating furnace (not shown), and then reduction treatment is performed at a temperature below the Curie temperature of the lithium tantalate crystal.
[0042] The mixing ratio (mass%) of Al powder and Al2O3 powder is preferably in the range of 1:99 to 50:50, the treatment temperature (reduction temperature) is preferably 580°C or higher, lower than the Curie temperature of lithium tantalate crystal (lower than about 600°C), and the treatment time (reduction time) is preferably several hours to several tens of hours. The heat treatment atmosphere is an atmosphere in which an inert gas is sealed, or an atmosphere in which an inert gas is continuously supplied and discharged into the heating furnace under atmospheric pressure. However, when the inert gas is sealed, the heat in the heating furnace may accumulate in one place, causing uneven reduction. For this reason, the heat treatment atmosphere is preferably an atmosphere in which an inert gas is continuously supplied and discharged into the heating furnace under atmospheric pressure. By continuously supplying and discharging the inert gas into the heating furnace, the heat can be made uniform in the furnace. The inert gas can be argon gas, nitrogen gas, or the like, and the flow rate of the inert gas continuously supplied and discharged into the heating furnace is preferably 0.5 to 5 L / min when the inert gas is argon gas. EXAMPLES
[0043] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the technical scope of the present invention is not limited to the following examples in any way.
[0044] (1) Configuration of the heating furnace The heating furnace used in the examples and comparative examples was provided with an air inlet and an exhaust port, and was filled with argon gas (oxygen partial pressure 1×10 -6Argon gas (approximately 1 atm) is continuously supplied into the furnace through the air inlet, and the argon gas is continuously exhausted to the outside of the furnace through the exhaust port, so that the inside of the furnace is adjusted to atmospheric pressure by replacing with argon gas. The flow rate of argon gas supplied to and exhausted from the furnace is set to 1 to 2 L / min.
[0045] However, during the annealing step described below, the argon gas is not supplied to or exhausted from the heating furnace, and the inside of the heating furnace is filled with air and adjusted to an atmospheric pressure atmosphere.
[0046] (2) Growth and slicing of LT single crystals Using a raw material with a congruent composition, a LT single crystal with a diameter of 4 inches was grown by the Czochralski method. The growth atmosphere was a nitrogen-oxygen gas mixture with an oxygen concentration of about 3%. The grown LT single crystal was transparent and pale yellow in color.
[0047] Next, the ends of the single crystal, which were insufficient in diameter while in the ingot state, were cut off, and heat treatment and poling treatment (polarization treatment) were performed to remove distortion. Furthermore, it was cylindrically ground to be processed into a cylinder slightly thicker than the final product, and the LT single crystal was sliced using the free abrasive method with the multi-wire saw device shown in Figure 3 to obtain multiple single crystal wafers.
[0048] The slurry (manufactured by Palace Chemical Co., Ltd.) used in the loose abrasive method contained SiC abrasive grains, an oil agent for dispersing the abrasive grains, and water.
[0049] The volume resistivity of the sliced single crystal wafer is 1×10 15 The electrical conductivity was Ω·cm and the Curie temperature was 603°C.
[0050] [Example 1] (Annealing process) As shown in FIG. 1, a plurality of single crystal wafers 1 were stacked to form a single crystal wafer polymer 10, and three sets of the single crystal wafer polymers 10 were placed on a stainless steel tray 2. The stainless steel tray 2 on which the three sets of the single crystal wafer polymers 10 were placed was then placed in a heating furnace filled with air and under atmospheric pressure to perform an annealing treatment of the single crystal wafers 1.
[0051] The annealing temperature was 500° C. and the annealing time was 24 hours.
[0052] (Reduction process) The single crystal wafers 1 that had undergone the annealing process were embedded in a mixture of 10% by mass of aluminum powder (Al powder) and 90% by mass of aluminum oxide powder (Al2O3 powder) filled into an aluminum container 21, and the multiple aluminum containers 21 (four in FIG. 2) in which the single crystal wafers 1 were embedded were housed in a large container 23 made of carbon, and the large container 23 was placed in the above-mentioned heating furnace. After that, commercially available argon gas was continuously supplied and exhausted into the heating furnace at a flow rate of 2 L / min under atmospheric pressure, and a reduction process was performed at 580°C (reduction temperature) for 20 hours (reduction time).
[0053] Then, the same reduction treatment was carried out on 200 single crystal wafers, and the volume resistivity of the single crystal wafers after the treatment was measured, and the incidence of color unevenness was investigated.
[0054] The volume resistivity is measured by a three-terminal method in accordance with JIS K-6911.
[0055] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 8.7% at Ω·cm (average value of 200 LT substrates, same below).
[0056] The results are shown in Table 1 below.
[0057] [Example 2] The sliced single crystal wafer was subjected to annealing and reduction treatment under the same conditions as in Example 1, except that the mixing ratio of Al powder in the reduction step was 20 mass % Al powder and 80 mass % Al2O3 powder.
[0058] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 9.0% in Ω·cm.
[0059] These results are also shown in Table 1 below.
[0060] [Example 3] The sliced single crystal wafer was subjected to the annealing treatment and reduction treatment under the same conditions as in Example 1, except that the annealing time in the annealing step was set to 40 hours.
[0061] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 3.6% in Ω·cm.
[0062] These results are also shown in Table 1 below.
[0063] [Example 4] The sliced single crystal wafer was subjected to annealing and reduction treatment under the same conditions as in Example 3, except that the mixing ratio of Al powder in the reduction step was 20 mass % Al powder and 80 mass % Al2O3 powder.
[0064] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 2.2% in Ω·cm.
[0065] These results are also shown in Table 1 below.
[0066] [Example 5] The sliced single crystal wafer was subjected to the annealing treatment and reduction treatment under the same conditions as in Example 1, except that the annealing temperature in the annealing step was set to 580°C.
[0067] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 2.5% in Ω·cm.
[0068] These results are also shown in Table 1 below.
[0069] [Example 6] The sliced single crystal wafer was subjected to annealing and reduction treatment under the same conditions as in Example 5, except that the mixing ratio of Al powder in the reduction step was 20 mass % Al powder and 80 mass % Al2O3 powder.
[0070] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 1.9% in Ω·cm.
[0071] These results are also shown in Table 1 below.
[0072] [Example 7] The sliced single crystal wafer was subjected to the annealing treatment and reduction treatment under the same conditions as in Example 5, except that the annealing time in the annealing step was set to 40 hours.
[0073] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 0.9% in Ω·cm.
[0074] These results are also shown in Table 1 below.
[0075] [Example 8] The sliced single crystal wafer was subjected to annealing and reduction treatment under the same conditions as in Example 7, except that the mixing ratio of Al powder in the reduction step was 20 mass % Al powder and 80 mass % Al2O3 powder.
[0076] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×109 The incidence rate of color unevenness due to white and black spots was 0.8% in Ω·cm.
[0077] These results are also shown in Table 1 below.
[0078] [Comparative Example 1] The sliced single crystal wafer was subjected to a reduction treatment under the same conditions as in Example 1, except that the annealing treatment of the single crystal wafer was omitted.
[0079] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 The incidence rate of color unevenness due to white and black spots was 10.0% in Ω·cm.
[0080] These results are also shown in Table 1 below.
[0081] [Comparative Example 2] The sliced single crystal wafer was subjected to a reduction treatment under the same conditions as in Example 2, except that the annealing treatment of the single crystal wafer was omitted.
[0082] The volume resistivity of the single crystal wafer (LT substrate) after reduction treatment is 1×10 9 In Ω·cm, the incidence of color unevenness due to white and black spots was 11.5%.
[0083] These results are also shown in Table 1 below.
[0084] [Table 1]
[0085] [confirmation] (1) Compared to the "color unevenness occurrence rate (10.0%)" of Comparative Example 1 in which the mixing ratio of Al powder in the reduction step is 10 mass%, the "color unevenness occurrence rate" of Examples 1, 3, 5, and 7 in which the mixing ratio is 10 mass% is improved to 8.7%, 3.6%, 2.5%, and 0.9%, respectively. Similarly, compared to the "color unevenness occurrence rate (11.5%)" of Comparative Example 2 in which the mixing ratio of Al powder in the reduction process is 20 mass%, it is confirmed that the "color unevenness occurrence rate" of Examples 2, 4, 6 and 8 in which the mixing ratio is 20 mass% is improved to 9.0%, 2.2%, 1.9% and 0.8%, respectively.
[0086] (2) Regarding the influence of the "annealing temperature" and "annealing time" on the "occurrence rate of color unevenness," when the annealing temperature is 500°C, a comparison between Example 1 with an annealing time of 24 hours (8.7%) and Example 3 with an annealing time of 40 hours (3.6%), as well as a comparison between Example 2 with an annealing time of 24 hours (9.0%) and Example 4 with an annealing time of 40 hours (2.2%), confirms that the length of the "annealing time" has a significant effect.
[0087] (3) On the other hand, when the annealing temperature is 580°C, a comparison between Example 5, which has an annealing time of 24 hours (2.5%), and Example 7, which has an annealing time of 40 hours (0.9%), as well as a comparison between Example 6, which has an annealing time of 24 hours (1.9%), and Example 8, which has an annealing time of 40 hours (0.8%), confirms that the length of the annealing time does not have a significant effect on the "color unevenness occurrence rate" compared to when the annealing temperature is 500°C. [Industrial Applicability]
[0088] According to the present invention, reduction defects (insufficient reduction) known as white spots and reduction defects (excessive reduction) known as black spots can be avoided, and a lithium tantalate substrate having excellent electrical properties and no color unevenness (uneven reduction) can be stably produced. Therefore, the present invention has industrial applicability for use as a substrate material for surface acoustic wave elements (SAW filters). [Explanation of symbols]
[0089] 1. Single crystal wafer 2 Stainless Steel Trays 10 Single crystal wafer polymer 21 Aluminum container 22 Mixed powder 23 Large containers 50 Multi-wire saw device 51 Wire 52 Wire Row 53 Crystal holding part 53a Slice Bed 53b Sheet material 54 Nozzle 55 Saddle 60LT single crystal R Roller
Claims
1. A method for producing a lithium tantalate substrate, comprising: a slicing step of slicing a lithium tantalate single crystal to obtain a single crystal wafer; and a reduction step of reducing the obtained single crystal wafer, A method for producing a lithium tantalate substrate, comprising the steps of: providing an annealing step, between the slicing step and the reducing step, of annealing the single crystal wafer that has not been subjected to the reducing treatment in an air atmosphere at a temperature of 500° C. or higher and lower than the Curie temperature of the lithium tantalate single crystal.
2. 2. The method for producing a lithium tantalate substrate according to claim 1, characterized in that a plurality of single crystal wafers are stacked to form a single crystal wafer polymer, and one or more single crystal wafer polymers are placed on a plate or tray, and then the plate or tray on which the single crystal wafer polymer is placed is placed in a heating furnace in an atmospheric environment to perform the annealing treatment.
3. 3. The method for producing a lithium tantalate substrate according to claim 1, wherein the annealing step is carried out for a period of 24 to 48 hours.
4. 4. The method for producing a lithium tantalate substrate according to claim 1, wherein the slicing step is a slicing process using a wire saw.
5. 5. The method for manufacturing a lithium tantalate substrate according to any one of claims 1 to 4, characterized in that the reduction step is a reduction treatment in which the single crystal wafer is embedded in a mixed powder of aluminum powder and aluminum oxide powder filled in a container, the container is placed in a heating furnace, and then heated at a temperature lower than the Curie temperature of the lithium tantalate single crystal.
6. 6. The method for producing a lithium tantalate substrate according to claim 5, wherein the reduction treatment is carried out while continuously supplying and discharging an inert gas into the heating furnace under an air atmosphere.
Citation Information
Patent Citations
Lithium niobate crystal or lithium tantalate crystal having enhanced performance to decrease charge on crystal surface and method to preliminarily control that kind of crystal
JP1999092147A
Production method of lithium tantalate substrate
JP2019202919A
Manufacturing method of lithium tantalate substrate
JP4063191B2
Process for producing lithium tantalate crystal
WO2004079061A1
